El impuesto predial y la inversión inmobiliaria En el Perú - Acosta Bernedo, Otto Alonso; Montenegro Monteza, Favio (Pontificia Universidad Católica del Perú, 2016)
In the present article, the authors analyze the issues related to the Property Taxation on venues that have urban habilitation and/or buildingprojects.In order to accomplish that, the authors examine the basis of the right to build, describe the stages of the constructive administrative procedure as regulated in Law 29090 and, finally, comment on the recent precedent of the Tax Court whichregards the matter.

En el presente artículo, los autores analizan la problemática del Impuesto Predial respecto de predios que cuentan con proyectos de habilitación urbana y/o edificación. Para ello, los autores examinan el fundamento del derecho a construir, describen las etapas del procedimiento administrativo constructivo regulado en la Ley 29090 y, finalmente, comentan el reciente precedente del Tribunal Fiscal al respecto.
Property taxation and real estate investment in Perú
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01